The Gnat and Other Minor Poems of Virgil - Virgil (University of California Press, 2011)
These delightful poems-by turns whimsical, beautiful, and vulgar-seem to have primarily survived because they were attributed to Virgil. But in David R. Slavitt's imaginative and appealing translations, they stand firmly on their own merits. Slavitt brings to this little-known body of verse a fresh voice, vividly capturing the tone and style of the originals while conveying a lively sense of fun.
10.1525/9780520949997